Efecto otoprotector de N acetilcisteína en pacientes sometidos a quimioterapia con cisplatino. Revisión de la literatura - Rubio M., Fabián; Torrente A., Mariela (Revista Hospital Clínico Universidad de Chile, 2015)
The aim of this publication is to update information regarding auditory damage caused by cisplatin and its possible prevention with N acetylcysteine (NAC). Cisplatin is a drug used in the treatment of various cancers. It has various adverse effects including ototoxicity. Ototoxicity manifests as sensorineural high tone hearing loss variable intensities, usually bilateral, irreversible, and occurs primarily owing to the formation of oxygen derived free radicals that trigger apoptosis. High frequency audiometry and distortion-product otoacoustic emissions are the most sensitive tests for the detection of cisplatin ototoxicity and they are comparable. NAC is a thiol compound used as a mucolytic that can prevent ototoxicity by several mechanisms . In vitro, it has been shown to decrease the damage of inner ear hair cells and auditory neurons . In humans, oral and intratympanic NAC has been tested concomitant tocisplatin chemotherapy with variable results, tending to show less hearing damage produced by cisplatin.